APPLICATION OF APPROPRIATE SKILL APPROACH BASED STRUCTURE ANALYSIS PROGRAM TO IMPROVE STUDENTS AND ACHIEVEMENTS STUDENT LEARNING - Hidayati Hidayati; Alexon Alexon; Turdjai Turdjai (UNIB Press, 2017)
This research aimed to describe the application of skill Approach Process Base on Struture Analysis Program , so as to increase the careful, achievement, the effectiveness of the students class X technique building at SMKN 1 Curup. This research method is a combination with exploratory sequential design. The subject of research for this class action research is X technique building at SMKN 1 Curup. The results was concluded that the implementation of application of Skill Approach Process base on Struture Analysis Program can improve student careful , the implementation of application of Skill Approach Process base on Struture Analysis Program to improve student learning achievement , the implementation of application of Skill Approach Process base on Struture Analysis Program can improve effective student learning achievement in subjects Statics and Tension class X technique building at SMKN 1 Curup.Keywords : pkp, sap, achievement, careful